Crashworthiness and energy absorption of UHPFRC-steel composite sandwich structures under impact loading. (1st May 2023) - Fan, Wei; Xie, Ruihong; Davidson, Michael; Yin, Hanfeng; Lai, Keyu; Wu, Qinglin
Highlights: Twelve different steel core structures are tested under drop-hammer impact tests. Measured dynamic responses were observed to differ by type of sandwich structure. Detailed FE models were developed and validated by the drop-hammer impact tests. Sandwich structures with strong energy absorption stability were identified. The results of multi-objective optimization show that the HT-F is most suitable for engineering applications. Abstract: This study aims to explore the dynamic crushing behaviors of a series of sandwich structures with varying configurations, which are composed of ultra-high performance fiber reinforced concrete (UHPFRC) face sheets and cores of steel and polyurethane (PU) foam. Drop-hammer impact tests were performed on 12 sandwich structure specimens, including four types (traditional frame (TF), ectopic frame (EF), corrugated plate (CP), and horizontal tube (HT)). The force profiles of EF type and HT type, compared with the other types, possessed low peak impact force (PIF) and high plateau force under the same impact energy. Test results indicated that the polyurea sprayed on the UHPFRC face did not affect the crashworthiness. Increases in core thickness can improve mean crushing force (MCF). The crashworthiness of the sandwich structure without the UHPFRC face sheet was weakened. The values of peak crushing force (PCF), MCF, energy absorption (EA), and specific energy absorption (SEA) under dynamic loading were greater than those in quasi-static loading. Finite element (FE) models were developed, validated, used to explore the energy absorption behavior in detail, and proved that EF-type and HT-type structures possess strong energy absorption stability. The multi-objective optimization showed that the HT-F structure is more suitable for practical applications.